(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This present study investigates the effect of replacing fishmeal with varying levels of Beni seed (Sesamum indicum) meal on the diet of Clarias gariepinus. Three hundred and sixty (360) healthy C. gariepinus (African mud catfish) were stocked in eighteen (18) experimental tanks and fed different graded levels of diets that were developed to contain 40% crude protein using graded levels of sesame seed meal (0%, 25%, 50%, 75%, and 100%) as a replacement of fish meal. Proximate compositions of both diets and fish carcasses were analyzed following the AOAC (2019) methods. Significant differences (p<0.05) were observed in moisture, ash, crude fibre, carbohydrate, fat, and crude protein contents among the treatments. Fish fed diets with 50% and 75% Beni seed inclusion (DT4 and DT5) demonstrated superior protein deposition compared to the control and other treatments. However, fish fed a 100% Beni seed diet (DT6) showed reduced ash and protein levels, indicating a nutritional limitation at complete substitution. This research concludes that partial replacement of fishmeal with Beni seed meal, particularly between 50% and 75%, is both nutritionally sound for C. gariepinus culture. Complete replacement (100%) may not support optimal growth due to reduced protein quality and the potential presence of anti-nutritional factors. Thus, incorporation of Beni seed meal up to 75% in fish feed is recommended. Further research may also be conducted on amino acid supplements, processing methods to minimize anti-nutritional value, and long-term performance to improve the practical use of Beni seed meal in aquaculture.